Acoustic wave based MEMS devices for biosensing applications - Voiculescu, Ioana; Nordin, Anis Nurashikin (Elsevier, 2012)
This paper presents a review of acoustic-wave based MEMS devices that offer a promising technology platform for the development of sensitive, portable, real-time biosensors. MEMS fabrication of acoustic wave based biosensors enables device miniaturization, power consumption reduction and integration with electronic circuits. For biological applications, the biosensors are integrated in a microfluidic system and the sensing area is coated with a biospecific layer. When a bioanalyte interacts with the sensing layer, mass and viscosity variations of the biospecific layer can be detected by monitoring changes in the acoustic wave properties such as velocity, attenuation, resonant frequency and delay time. Few types of acoustic wave devices could be integrated in microfluidic systems without significant degradation of the quality factor. The acoustic wave based MEMS devices reported in the literature as biosensors and presented in this review are film bulk acoustic wave resonators (FBAR), surface acoustic waves (SAW) resonators and SAW delay lines. Different approaches to the realization of FBARs, SAW resonators and SAW delay lines for various biochemical applications are presented. Methods of integration of the acoustic wave MEMS devices in the microfluidic systems and functionalization strategies will be also discussed.